De-radicalisation in the UK prevent strategy: security, identity, and religion - Elshimi, M. S. (Routledge critical terrorism studies, 2017)
The enigma of de-radicalisation -- Radicalisation as the "new security challenge" -- The concept of de-radicalisation : an analysis of research data -- An alternative concept : de-radicalisation as the "technologies of the self ' -- Discursive technology (truth) : the production of radicalisation -- Disciplinary technology (power) : surveillance, detection, discipline -- Confession technologies (identity) : "salvation in this life" -- Implications and a new strategy for engagement -- Overton Windows